Analysis of macrobenthic assemblages and ecological health of Yellow River Delta, China, using AMBI & M-AMBI assessment method. Issue 2 (30th June 2017) - Li, Baoquan; Li, Xiaojing; Bouma, Tjeerd J.; Soissons, Laura M.; Cozzoli, Francesco; Wang, Quanchao; Zhou, Zhengquan; Chen, Linlin
Abstract: Yellow River delta (YRD) is a typical example of a valuable coastal ecosystem that is under increasing anthropogenic threat in China. To understand the current health status of this region, three surveys in 2011 for the abiotic conditions and macrobenthic assemblages were performed. The concentration of trace metals were relatively low in the sediment at all sampling stations representing a good sediment quality. A total of 159 macrobenthic species were identified during the three surveys. ABC curves showed that the macrobenthic fauna at 8 sampling stations suffered disturbances from human activities. M-AMBI index indicates that the benthic ecological quality of YRD is currently still not in a good condition. Five trace metals, water temperature and depth were the main environmental variables affecting the distribution pattern of macrobenthic assemblages. Community succession has occurred over the past 60 years, as evidenced by changes of species composition, key species, distribution pattern and range. Highlights: Surveys for the abiotic conditions and macrobenthic fauna were performed in YRD. M-AMBI index indicates that the benthic ecological quality of YRD is not good. Five trace metals, water temperature and depth were the key environmental factors. Community succession has occurred in YRD over the past 60 years.